Mitigating drought stress and enhancing maize resistance through biopriming with Rhizopus arrhizus: insights into Morpho-Biochemical and molecular adjustments - Asmaa S. Taha; Hoda A. Fathey; Asmaa H. Mohamed; Amira A. Ibrahim; Mohamed Abdel-Haleem (BMC Plant Biology)
Abstract Background Drought stress represents a significant threat to crop productivity, particularly in regions characterized by water scarcity. This study investigated the potential of utilizing endophytic fungi to enhance drought tolerance in maize (Zea mays L.). Specifically, we aimed to investigate the role of these fungi in improving the physiological, morphological, and molecular responses of maize plants subjected to drought conditions. Results Our findings revealed a significant contribution of endophytic fungi in mitigating the adverse effects of drought stress. Morphological analysis revealed higher root and shoot growth in treated plants compared to untreated controls, indicating improved water uptake and retention capabilities. Furthermore, physiological parameters, including chlorophyll content, markedly increased in fungus-treated plants under drought conditions. The activities of enzymatic antioxidants, including catalase (CAT), peroxidase (POX), and polyphenol oxidase (PPO), in maize plants inoculated with R. arrhizus under severe drought stress conditions were increased by 157.71%, 92.14%, and 144.44%, respectively, compared to those of the non-bioprimed plants. Endophytic inoculation resulted in a reduction of H₂O₂ and MDA levels by 48% and 55.11%, respectively, compared to non-inoculated plants. At the molecular level, ISSR analysis revealed distinct banding patterns between inoculated and non-inoculated plants under drought stress, indicating genomic variation linked to the presence of endophytic fungi. These molecular fingerprints suggest the activation of stress-responsive pathways and highlight the potential role of endophytes in enhancing plant drought tolerance. Collectively, these results highlight the potential of utilizing endophytic fungi as a sustainable and eco-friendly approach to enhance drought tolerance in maize, offering promising implications for agricultural practices in arid and semiarid regions. Conclusions This study represents one of the few investigations detailing the practical application of endophytic fungi-especially Rhizopus arrhizus, in mitigating the detrimental effects of drought stress caused by limited water availability. These findings raise the possibility of utilizing endophytes suited to dry environments within agricultural systems.